Shift work and cardiovascular strain on working and non-working days. (17th August 2022) - Stieler, L; Hunger, B; Seibt, R
Abstract: Background: Shift work is often associated with adverse effects on cardiovascular health of employees. Only a few studies address the strain of shift and day workers on non-working days compared to working days. Aims: This study aims to determine how the cardiovascular strain of hotel and catering industry (HCI) employees who work alternating shifts differs from those working normal day shifts—on both a working day (WD) and a non-working day (ND). Methods: The sample consisted of 60 alternating shift (morning and afternoon, mean age: 31.5 ± 8.5 years) and 88 day workers (mean age: 35.3 ± 9.4 years). A 24-h ambulatory measurement of blood pressure (BP) and heart rate (HR) on WD and ND with the time phases DAY, SLEEP, and 24-h TOTAL was used to analyse cardiovascular strain. BP status was assessed by self-measurement (36% hypertensives). Results: The total strain over 24 h was slightly higher on WD than ND (mean BP: 134/79 versus 127/75 mmHg, P = 0.002–0.020; mean HR: 78 versus 75 bpm, P = 0.055). In trend, shift workers had higher systolic BP than day workers during the individual time phases of DAY, SLEEP, and 24-h TOTAL on WD. Known cardiovascular risk factors emerged as critical determinants of cardiovascular strain: older age, male gender, and hypertensive blood pressure status. Conclusions: The results revealed no clear association between the alternating shift system in HCI and increased cardiovascular strain. The 24-h ambulatory measurement is considered ideal for determining cardiovascular strain in everyday life and under working conditions. Abstract : This study aimed to determine cardiovascular strain of alternating shift and day workers of the hotel and catering industry—on both a working day and a non-working day. The total strain over 24 h was slightly higher on the working day compared to the non-working day. In trend, shift workers had higher systolic blood pressure than day workers. Known cardiovascular risk factors emerged as critical determinants of cardiovascular strain.